Analisis Daya Saing Ekspor Udang Indonesia ke Delapan Negara Tujuan Terbesar Tahun 2000–2019 - Fath Esa Prasanti Kusuma; Liza Kurnia Sari (Politeknik Statistika STIS, 2021)
According to Un Comtrade data in 2019, the eight largest shrimp export destinations absorbed more than 90 percent of Indonesia's shrimp. However, the contribution of Indonesian shrimp to these eight countries is very low. Therefore, this research was conducted to determine the competitiveness and the factors that influence Indonesian shrimp exports. This research used panel data of 8 largest destination countries during 2000–2019. Analysis method that used is RCA analysis and panel data regression with a gravity model approach. The variable in this research is volume of shrimp exports, real export prices, REER, population of destination countries, GDP constant of destination countries, and economic distance. The results show that the competitiveness of Indonesian shrimp is above the world average except in Thailand. In addition, it was found that economic distance, REER, and price had a significant effect on Indonesia's shrimp exports to the eight biggest destinations